Pengembangan Instrumen Investment Readiness Sebagai Pedoman Penilaian Kesiapan Pendanaan Start-Up Di Era Ekonomi Digital - Denies Priantinah; Ratna Candra Sari; Patriani Wahyu Dewanti; Arin Pranesti (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This research aims to develop instruments to measure start-up funding assessments. The dimensions of measuring funding and Investment readiness consist of eight dimensions adopted from the investment guide. Methodology/approach: This research is based on solving specific problems by improving the instructional design process and developing new models, tools and procedures regarding Investment readiness instruments as guidelines for assessing start-up funding readiness in the digital economy era. An investment readiness instrument is advanced by holding a Focus Group Discussion (FGD) with experts in start-up investment. Findings: The results of this study contribute to developing an investment readiness instrument as a guideline for assessing start-up funding readiness for the start-up. Practical implications: The practical implication of this research is that investment readiness instruments can assist start-ups in assessing financial and non-financial performance, which is helpful for funding applications and start-up financing. Originality/value: This research has social implications for investors and creditors in order to make relevant decisions regarding investment and funding for start-ups.